Rencana Mitigasi Dan Kesiapsiagaan Badan Penanggulangan Bencana Daerah Bojonegoro Untuk Menangani Bencana Kekeringan - Amanda, Septiani (Universitas Bojonegoro, 2023)
Abstract: The research was carried out at the Bojonegoro Regency Regional Disaster Management Agency (BPBD) which aims to determine the distribution of villages affected by drought in Bojonegoro Regency in 2019-2020 and to find out how the BPBD handles drought emergencies, as well as to find out BPBD's mitigation and preparedness plans for deal with an impending drought. The method used is participation and literature study. From the research results, it was found that in 2019 as many as 15 villages from 11 sub-districts in Bojonegoro Regency began to experience a clean water crisis during the dry season and in 2020. BPBD Bojonegoro Regency noted that 16 sub-districts in Bojonegoro Regency were affected by drought. To overcome the drought disaster in 2019 BPBD prepared 500 clean water tanks and held the establishment and training of 2022 Disaster Resilient Villages in several villages, one of which is Malingmati and Jatimulyo Villages, Tambakrejo District. From 23 July to 14 October 2019 BPBD has distributed 928 trips of clean water to deal with drought in Bojonegoro Regency. During the pre-dry season, the BPBD is building ponds, biopores, infiltration wells, and 142 water towers and drilling wells in 13 locations. In an effort to realize community resilience in dealing with disasters, BPBD Bojonegoro Regency held training and the formation of Disaster Resilient Villages in several villages. This is done in an effort to form a direct synergy with the community in anticipating potential natural disasters. Keywords: Regional Disaster Management Agency; Drought, Mitigation and Preparedness Abstrak: Penelitian dilaksanakan di Badan Penanggulangan Bencana Daerah Kabupaten Bojonegoro (BPBD) yang bertujuan untuk mengetahui sebaran desa yang terkena dampak kekeringan di Kabupaten Bojonegoro pada tahun 2019-2020 dan untuk mengetahui bagaimana cara BPBD menangani darurat bencana kekeringan, serta untuk mengetahui rencana mitigasi dan kesiapsiagaan BPBD untuk menangani bencana kekeringan yang akan datang. Metode yang digunakan adalah partisipasi dan studi literatur. Dari hasil penelitian di dapatkan bahwa pada tahun 2019 sebanyak 15 desa dari 11 Kecamatan di Kabupaten Bojonegoro mulai mengalami krisis air bersih pada musim kemarau dan pada tahun 2020. BPBD Kabupaten Bojonegoro mencatat ada 16 Kecamatan di Kabupaten Bojonegoro terdampak bencana kekeringan. Untuk mengatasi bencana kekeringan pada tahun 2019 BPBD menyiapkan 500 tangki air bersih dan menggelar pembentukan serta pelatihan Desa Tangguh Bencana tahun 2022 di beberapa Desa, salah satunya Desa Malingmati dan Jatimulyo Kecamatan Tambakrejo. Sejak 23 Juli-14 Oktober 2019 BPBD telah mendistribusikan sebanyak 928 rit air bersih untuk menangani bencana kekeringan di Kabupaten Bojonegoro. Untuk pra kemarau BPBD melakukan pembuatan embung, biopori, sumur resapan, dan 142 buah water tower dan pembuatan sumur bor di 13 lokasi. Dalam upaya untuk mewujudkan ketangguhan masyarakat dalam menghadapi bencana BPBD Kabupaten Bojonegoro menggelar pelatihan dan pembentukan Desa Tangguh Bencana di beberapa Desa. Hal tersebut dilakukan dalam upaya membentuk sinergi langsung dengan masyarakat dalam mengantisipasi potensi bencana alam. Kata kunci: Badan Penanggulangan Bencana Daerah; Kekeringan, Mitigasi dan Kesiapsiagaan